Pertumbuhan Ekonomi di Kawasan Wilayah Sulawesi dengan Pendekatan Data Panel Tahun 2012-2022 - Dedi Mardianto (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
Economic growth is a measure of the effectiveness of economic activities and is important in any country. Therefore, the objectives of this research are (1) to determine the impact of foreign investment on economic growth, (2) to determine the impact of domestic investment on economic growth, and (3) to determine the impact of poverty levels on economic growth. . It's about determining the impact. Sulawesi region. The data used in this discussion are cross- sectional and time-series data from 2012 to 2022 obtained from the Central Statistics Agency (BPS). Next, analysis was carried out using quantitative methods with a panel data regression approach. The research results show that the variable foreign investment and domestic investment partially (t test) has a significant positive influence on Sulawesi's economic growth, while the poverty level variable has a negative but not significant influence on Sulawesi's economic growth. It turns out it gives. Meanwhile (F test) the variables foreign investment, domestic investment and poverty level have a significant influence on the economic growth of the Sulawesi region. Therefore, the Government needs to strengthen the investment climate and improve labor quality to make economic growth more inclusive and able to absorb more workers.